Modalities of treatment for Nevus depigmentosus: review of the literature - Saad Altalhab (Taylor & Francis Group, 2023)
Background Nevus depigmentosus (ND) is one of the pigmentary conditions that is characterized by a hypopigmented patch with an irregular border. It is usually present at birth or shortly after birth. It is not a progressive condition, but it may increase in size in proportion to the growth of the body. Despite many treatment modalities, there is no effective treatment for this condition. Objective To review all articles about the treatment options for ND. Methods Pubmed database were searched for this study, and relative clinical trials were included in the review. Descriptive findings, including age, gender, and treatment modality and response, were reported. Results A total of 62 articles were identified, and 16 relevant articles were included in this review after screening and removing the duplicates. Conclusion In the literature, a limited number of treatment modalities have been employed for ND. Among these, surgical interventions and phototherapy have been the most commonly studied, but their efficacy has varied. Unfortunately, there is no definitive cure for ND, and recurrence of the lesion is not an uncommon occurrence even after complete clearance. Furthermore, there is a dearth of large-scale clinical studies that comprehensively analyze the different treatment modalities for ND.